Clients’ knowledge and satisfaction with outpatient pharmacy services and associated factors at Felege Hiwot comprehensive specialized hospital, Ethiopia: A cross-sectional study - Firdawek Shenkute Ergetie; Abebe Tarekegn Kassaw; Eyayaw Ashete Belachew (SAGE Open Medicine, 2024)
Objective: This study aimed to assess patient knowledge and satisfaction and associated factors with outpatient pharmacy service at Felege Hiwot comprehensive specialized hospital. Design, setting and participants: An institution-based cross-sectional study was conducted at Felege Hiwot comprehensive specialized hospital on patients getting outpatient Pharmacy service from 01 March 2022 to 30 May 2022. The study participants were selected by simple random sampling method. Main outcome measured: Patients’ knowledge and satisfaction with pharmacy service was measured by a structured questionnaire and Data were collected, cleared, and coded, then entered into EPI Info (Epidemiological information. version 7.1.5.2) and analyzed using SPSS (version 25). Results: The overall knowledge result of the respondents showed that only 13.3% of individuals have good drug knowledge and 72.01% of respondents were satisfied with the outpatient pharmacy service. Following up on the multivariate analysis of service modality patients by credit (AOR: 5.50 (1.71–17.74), who are with the occupation of merchants (AOR: 0.09 (0.01–0.83)) and labeling (AOR: 3.13 (1.58–6.20) had an association with drug knowledge. Multivariate analysis showed that waiting time, dispensing time and privacy had an association with satisfaction. When we consider waiting time; respondents with 3–6 min, 6.1–9 min and >9 min waiting times are 0.06 times, 0.02 times, and 0.01 less likely satisfied compared with respondents having waiting time <3 min. It shows that as the patient stays without getting serviced for a long time, satisfaction decreases. Conclusions: Overall, around three-fourths of the respondents were satisfied with the outpatient pharmacy services which is approaching the national satisfaction assessment result. Respondents were strongly satisfied with Dose, route, frequency, and duration. However, they were strongly dissatisfied with the name of the drug. After the multivariate analysis privacy, waiting time, and dispensing time had an association with patient satisfaction.